FORMULATING A COLLABORATIVE ISLAMIC RELIGIOUS EDUCATION THEORY: TOWARD STRENGTHENING RELIGIOUS MODERATION IN EDUCATIONAL INSTITUTIONS: Qualitative Research: Literature Study - Ahmadan Ahmadan Haquridha Yasyada; Liza Jauharotul Munfarida Al Khurriyyah; Muhammad Wasith Achadi; Nur Hidayat (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This article aims to formulate a collaborative theory of Islamic Religious Education (IRE) that can systematically and sustainably strengthen religious moderation in educational institutions. In the context of Indonesia's religious and cultural diversity, religious moderation is essential for fostering a harmonious and just society. This study employs a literature review method with a theoretical approach, analyzing concepts such as wasathiyyah, moderate Islamic values, and educational policies. The findings reveal that the implementation of religious moderation in education can be achieved through integrating tolerance values into the curriculum, optimizing inclusive teaching methods, teacher training, and evaluating students’ attitudes. The proposed collaborative IRE framework emphasizes the integration of Islamic, national, and socio-cultural values, while promoting key principles such as honesty, openness, compassion, and flexibility. Consequently, educational institutions serve as strategic spaces for shaping a generation that is moderate, tolerant, and capable of living peacefully in diversity.